Gender Equality and Electoral Violence in Africa : Unlocking the Peacemaking Potential of Women - Ouedraogo, Rasmane (IMF Working Papers; Working Paper ;, 2019)
We examine the impact of gender equality on electoral violence in Africa using micro-level data from the sixth round of Afrobarometer surveys. The sample covers 30 countries. We find that gender equality is associated with lower electoral violence. Quantitatively, our estimates show that an increase in female-to-male labor force participation ratio by 1 percentage point is correlated with a reduction of the probability of electoral violence across the continent by around 4.2 percentage points. Our results are robust to alternative ways to measure electoral violence and gender equality, as well as to alternative specifications. The findings of this paper support the long-standing view that women empowerment contributes to the reduction of violence and underscore the urgency of addressing gender inequality in Africa.